Electrolysis - Linkov, Vladimir; Kleperis, Janis (IntechOpen, 2012)
Asking Google for different applications of electrolysis, interesting results can be noticed: electrolysis and hair removal - about 284 000 000 web pages, water electrolysis - about 7 440 000 web pages and industrial electrolysis - about 2 540 000 results. In this book three most important applications of technological electrolysis are discussed - water electrolysis (hydrogen production), industrial electrolysis and environmental electrolysis. Authors of the chapters are recognized specialists in their respective research fields and the presented material is not only from reviews and literature sources, but also original results. We hope that the reader will find useful information in the chapters of this book and are certain that the science can reveal unexpected discoveries even tomorrow, if current progress is at hand or on a shelf.